Dual-career through the elite university student-athletes` lenses: The international FISU-EAS survey - Condello, G.; Capranica, L.; Doupona, M.; Varga, K.; Burk, V. (PLOS ONE, 2019)
Athletes have the right to combine their sport and higher education careers (e.g., dual career), but differences in the recognition of the student-athlete`s status and availability of dual career programmes and services exist worldwide. The purpose of this study was to investigate the dual career phenomenon through the international student-athletes` views. Student-athletes competing at the 2017 Summer Universiade were recruited to respond a 31-item online survey encompassing demographic characteristics (Q1-8), sport and university engagement (Q9-13), student-athletes` knowledge and possible sources of information regarding dual career (Q14-22); and dual career support at personal, sport, and academic levels (Q23-31). Four hundred twenty-six respondents (males: 46%, females 54%), competing in 22 different sports (individual: 74%, team: 26%) from Africa (4%), America (20%), Asia (34%), Europe (39%), and Oceania (3), had experienced previous international sports events (94%). Differences among continents emerged for sport (p<0.001) and university (p = 0.039) engagement, and transfer time from home to the training venue (p = 0.030). Individual sports student-athletes showed higher sport engagement (p = 0.003) compared to team sports counterparts. Differences among university majors emerged for university engagement (p<0.001). Long absence from classes (57%), limited leisure time (50%), financial uncertainty (44%), reduction of training due to education (42%), and overload feelings (37%) emerged. The majority of the sample resulted not familiar with dual career programmes (60%) and public authorities (69%), envisaging national dual career policies at university (37%) and sport (25%) levels. Multiple relevant dual career supporters at personal, sport, and university levels were identified, mainly parents (86%) and coaches (65%). To strengthen the potential of the student-athletes of the future, a dual career network should be established among several stakeholders, for transnational cooperation and sharing of knowledge and best practices through extensive communication between policy-makers, practitioners and those having a strong supportive dual career role (e.g., parents, coaches, and university sport staff).